Steam as an approach for interactive learning of computer-aided design (Revista Cientifica Ingenio Magno, 2022)
STEAM (Science, Technology, Engineering, Arts and Mathematics) arises in theUnited States as a pedagogical approach for the identification and resolution of problemswhere a level of independence is granted to students with the purpose of having alearning classroom based on collaborative work and that can enhance the appropriationof concepts and topics that integrate skills and abilities in different disciplinary areas.From a descriptive, exploratory mixed approach, carried out with university students fromYopal Casanare who have seen the CAD Computer Aided Design course and where theappropriation of the concepts and competences expected in engineering training areaspresents a certain degree of difficulty, elements of the model are applied to achieve aninteractive learning of the subject through research processes and the use of educationalrobotics that allow better academic results, placing the student as a dynamic, participativeactor, with the capacity to innovate, create and transform real needs into specific solutions,being the starting point for teachers and directors in the linking of good educationalpractices through the incorporation of contents and learning tools for the strengthening ofskills and competencies in the professional work of the engineer.
Keywords: STEAM, Interactive learning, Educational robotics, CAD.